Fungsi Bahasa pada Konten Khotbah Pengkhotbah di Jemaat-Jemaat Lingkungan Kota Klasis Sentani - Daniel Wenda; Lewi Kabanga; Maryo Welly Labobar (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
We use language functions in various situations to achieve our purposes and meanings. Papuan Christianity life in the city, especially in GKI who live in Sentani, is educated by preachers’ sermons. This study aims to determine the language functions used by preachers in GKI churches in Sentani and their relations to the local education of Papua. This study used a qualitative method. The technique used to collect data was recording 12 samples in 4 weeks. The data was transcribed and reduced, and after that, indexed into the table as displayed data. The data was analysed based on the distribution of micro functions introduced by Leech. Firstly, the data was percentage to examine the dominance of language functions and then analysed by considering the phenomenon embodied. The results of this study reveal that the dominant language functions in preachers’ sermons are (1) informative, which consists of giving advice, lecturing, suggesting, and announcing; (2) the aesthetic function is signed with local language style and code-mixing/switching; (3) the expressive function demands the congregations’ attitude that indicates positive expression; (4) directive function is formed by request; (5) phatic function is constructed in the forms of contextual greetings, namely spirituality and local greeting of Papua.